THE EFFECT OF THE USE OF E-WALLET AND ECONOMIC LITERACY ON CONSUMPTIVE BEHAVIOR WITH A HEDONIC LIFESTYLE AS AN INTERVENING VARIABLE IN ECOJOMICS FACULTY STUDENTS OF THE STATE UNIVERSITY OF JAKARTA (A CASE STUDY IN THE CLASS OF 2022) - Ihsan, Tubagus; Sariwulan, Rd. Tuty; Nikensari, Sri Indah (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2023)
Consumptive behavior is the act of an individual to consume goods and services in excess, which prioritizes wants over needs. Through the development of information technology, students can carry out consumption activities through the palm of the hand, namely a smartphone telecommunications device. If students do not have an understanding of the finances of using e-wallet applications wisely and or poor economic literacy, students will be very easily influenced and carried away into consumptive behavior. The purpose of this study was to determine the factors that influence the consumptive behavior of students with a hedonic lifestyle as an intervening variable. The population of this research is all students of the Faculty of Economics class of 2020, Jakarta State University as many as 688 students. Samples were taken using the Slovin formula with an error rate of 5 percent as many as 253 students. The sampling technique used is stratified random sampling, taking sample members from the population at random because the members of the population are considered homogeneous. The data collection method used a questionnaire (Google Form). The data analysis method used is path analysis. The results showed that e-wallet and hedonic lifestyle had a positive and significant effect on consumptive behavior. Then economic literacy has a negative and significant effect on consumptive behavior. It was also found that the hedonic lifestyle was able to mediate the effect of e-wallet and economic literacy on consumptive behavior. Based on the results of the study, it can be concluded that the hedonic lifestyle is able to mediate the effect of e-wallet and economic literacy on consumptive behavior in students of the Faculty of Economics, State University of Jakarta batch 2020. Suggestions that can be given are students to be wiser in using e-wallet and not easily tempted. offered by e-wallet service providers and students must adhere to what educated people should believe so that they can avoid consumptive behavi